"Being attentive": exploring other-than-human agency in medicinal plants through everyday Rastafari plant practices. Issue 2 (3rd April 2018) - Nathen, Tihana
Abstract : The focus is on everyday practices and relations between local medicinal plants, Rastafari bossiesdokters [bush doctors] and kruiemanne [herbalists] of the Matzikama Local Municipality, which lies in the far north-west of the Western Cape Province. Inspired by the work of Bruno Latour, plants are approached as "actants" in an assemblage. Emphasising relational philosophies concerning human-plant interaction and drawing on the concept of gees [spirit], the paper illustrates some ways in which medicinal plants from the mountains appear to act with intentionality. I provide tentative suggestions to re-conceptualise and re-think engagement between plants and humans.